Altered expression profile of plasma exosomal microRNAs in exclusive electronic cigarette adult users - Dongmei Li; Zidian Xie; Sadiya Bi Shaikh; Irfan Rahman (Scientific Reports)
Abstract Little is known about how exclusive e-cigarette use affects exosomal microRNA (miRNA) expression, which is crucial in inflammation and disease processes like cancer. We compared exosomal miRNA profiles between exclusive e-cigarette users and non-users. We used plasma samples from 15 exclusive e-cigarette users and 15 non-users from the Population Assessment of Tobacco and Health (PATH) Wave 1 study (2013–2014) and sequenced miRNAs with Illumina NextSeq 500/550. We performed differential analyses using DESeq2 in R/Bioconductor, adjusting for race, and conducted gene enrichment analyses on target genes regulated by significant miRNAs. Further, molecular-based techniques using the miRNA mimics and inhibitors were applied for the validation of the expressions of the miRNAs in vitro. We identified four miRNAs that were upregulated in exclusive e-cigarette users compared to non-users: hsa-miR-100-5p, hsa-miR-125a-5p, hsa-miR-125b-5p, and hsa-miR-99a-5p, after adjusting for the confounding effects of race. However, none of the miRNAs remained statistically significant after controlling for the false discovery rate (FDR) at 5%. Subgroup analysis of White participants only identified four miRNAs (hsa-miR-100-5p, hsa-miR-125b-5p, hsa-miR-200b-3p, and hsa-miR-99a-5p) that were also upregulated in e-cigarette users with one miRNA hsa-miR-200b-3p remaining statistical significance after controlling for the FDR at 5%. GO enrichment analysis showed that these miRNAs are involved in processes like transcription regulation and cellular protein modification. KEGG pathway analysis indicated their involvement in cancer pathways, including small cell lung cancer, renal cell carcinoma, and signaling pathways (neurotrophin, ErbB, PI3K-Akt, FoxO, Hippo, MAPK, TGF-beta). Overexpression of hsa-miR-125b-5p promoted DNA damage in bronchial epithelial cells. These findings suggest an elevation of carcinogenic cellular signaling pathways in exclusive e-cigarette users.